The Future Of Accounting Profession in The Industrial Revolution 4.0: Meta-Synthesis Analysis - Rosi, Ni Made Kariana; Mahyuni, Luh Putu (E-Jurnal Akuntansi; Vol 31 No 4 (2021)DO - 10.24843/EJA.2021.v31.i04.p17, 2021)
Various appearances of applied technology, such as Artificial Intelligence (AI), Internet of Things (IoT), and Big Data are all Industrial Revolution 4.0 characteristics that can change the business model. This research aims to explore how the advancement of Industrial Revolution 4.0 technology might disrupt the accounting profession. This research applied meta-synthesis method. The results of this study illustrated that the importance of development in the accounting sector is to keep pace with technological advances in industry 4.0. This must be balanced with the development of knowledge in the field of accounting so that all types of development can be carried out as well as possible. The findings showed that the appearance of various kinds new technology had a very significant impact in the development of the accounting profession. Further research should be able to discuss the Industrial Revolution 4.0 impact in more depth and can be linked to other accounting professions, such as internal auditors. Keywords: Accounting Profession; Industrial Revolution 4.0; Technology.